THE POLITICAL ECONOMY OF TRADE LIBERALIZATION AND APEC GLOBAL AGENDA 2014: AN ANALYSIS FROM INDONESIA PERSPECTIVE - Setiyanto, Ari (Jurnal Pertahanan & Bela Negara, 2014)
The 25 years of APEC shows a positive correlation between trade and economic growth. The strong correlation makes APEC seen as a future core of economic power and potential to be a global leadership in the development of international norm, rules, and cooperation. International political economy concerns to how scarce resources are allocated to different uses and distributed among individuals through the process of decentralized market. It also refers to the handling of issues related to cross-national boundaries and relationships between two or more than two countries through a complex political process involving a country, bilateral relations between the countries, international organizations, regional alliances, and global agreements. In globalization era, improving quality of human resource and sustainable growth is required. However, under the pressure of the international competition, Indonesia poses a number of new challenges, economic as well as political. The Indonesian economic challenge is in investment in commercial infrastructure to support greater connectivity. The new vision to be the world maritime axis has been promoted from the President Joko Widodo. It is the momentum for Indonesia to take advantage from the APEC global agenda to strengthen Indonesian role in sustaining national, regional, and international economic growth through infrastructure development in maritime sector.Â Keywords: APEC, connectivity, regional integration, maritime axis, trade liberalization, globalization